Extraction and Composition of Volatiles from Concrete of Pandanus fascicularis Lam - K. Rout, Prasant; Naik, Satyanarayan; Ramachandra Rao, Y. (Asian Journal of Chemistry, 2010)
Kewda (Pandanus fascicularis Lam) flowers are commercially hydro distilled to obtain essential oil and attars. The oil is obtained usually in 0.03 to 0.04 % depending on the season and time elapsed between harvests and processing. Extraction with hexane on the other hand provides concrete in 0.315 % yields. Hydro distillation of concrete is found to give a steam volatile oil in nearly double the yield. The oil obtained was analyzed and reported the comparison of the composition with the essen-tial oil obtained in the conventional way.